Singapore : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report, 2009)
This 2009 Article IV Consultation highlights that Singapore has been severely affected by the global downturn. The collapse in external demand has led to a sharp contraction in GDP, which fell by almost 13 percent in the first quarter of 2009. Executive Directors have observed that the floating exchange rate regime has served Singapore well, and that the exchange-rate centered monetary policy framework has been an important source of stability in times of turbulence. They have commended the authorities for proactively implementing a series of measures to safeguard the stability of the financial system.